LITERARY FAIRY-TALE IN CONTEXT OF STUDY RESEARCHES OF LITERATURE - Dybovska , O. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article presents the personalities of literary tales researchers and considered the main directions of their research. The concepts of “fairy tale” and “literary fairy tale” are determined. Generalized concepts of storytellers and its causes are analyzed.